1A.12: GENETIC BACKGROUND OF FEMORAL ATHEROSCLEROTIC PLAQUE FORMATION. (June 2015) - Tarnoki, A.; Tarnoki, D.L.; Fejer, B.; Godor, E.; Molnar, A.A.; Horvat, P. Maurovich; Medda, E.; Fagnani, C.; Stazi, M.A.; Merkely, B.; Farina, F.; Baracchini, C.; et al.
Abstract : Objective: Femoral atherosclerosis, a major cause of peripheral artery disease, has been associated with higher cardiovascular risk in lower extremity peripheral arterial disease patients. The purpose of our study was to assess the effects of the heritable components of atherosclerotic plaque formation in the femoral artery. Design and method: 161 Hungarian and Italian twin pairs (n = 322, 75 Hungarian and 86 Italian pairs from Padua, Perugia and Terni; 83 monozygotic /MZ/, 78 dizygotic /DZ/; mean age 50 ± 13 years) recruited from the Hungarian and Italian Twin Registries underwent B-mode sonography of bilateral common and superficial femoral arteries (CFA, SFA). Concordance rates between members of the MZ and DZ pairs were calculated, and compared by Chi-square test. Rough heritability was analysed by Falconer formula. Results: Plaques were identified in 24% and 6% of patients in CFA and SFA, respectively. Significantly higher concordance rate was found in MZ twins compared to DZ pairs regarding the presence of plaques in CFA (rMZ = 0.869 vs. rDZ = 0.696) and SFA (rMZ = 0.622 vs. rDZ = 0.403) on left or right side, which indicated a 34% and 44% rough heritability, respectively. Conclusions: Femoral atherosclerotic plaque formation in CFA and SFA is moderately genetically determined. Further studies should elucidate whether offsprings of families at high risk for femoral atherosclerosis may benefit from early ultrasound screening.